PENGARUH LATIHAN DROP PASS AND SHOOTING DRILLS TERHADAP KETEPATAN SHOOTING DAN PASSING PEMAIN SEPAK BOLA PUTRA U-15 DI KLUB MAESTRO FC LOMBOK TIMUR TAHUN 2022 - Nova Dwi Kurnia, Subakti, Supriadin, dan Herman Syah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Problem Statement: Shooting skills are very important for players because it is impossible to score without it. Meanwhile, mastery of correct passing techniques and the application of efficient techniques can facilitate the passage of the ball between sides in order to achieve the goal (goal). Research objective: This study aims to determine the effect of drop pass and shooting drills on the accuracy of shooting and passing of U-15 male football players at the Maestro FC Club Lombok Timur in 2022. Research Design: The research design used in this study was